A Kantian ethics of paradise engineering. (15th November 2019) - Paez, Eze
Abstract: Wild animals probably have net negative lives. Christine Korsgaard rejects the view that we might engineer paradise by redesigning nature and animals so that they have the best possible existences. She believes the genetic changes required would not be identity-preserving, thereby causing animals to cease to exist. I argue, first, that paradise engineering is permissible. Many harms are caused by non-sentient natural entities and processes. Moreover, sentient animals can survive modifications compatible with their psychological persistence over time. Second, we are required to re-engineer nature in order to satisfy animals' right to the resources necessary for a reasonable life.